2016
DOI: 10.1007/s13365-016-0434-7
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E ε4 genotype status is not associated with neuroimaging outcomes in a large cohort of HIV+ individuals

Abstract: Previous neuroimaging studies suggest a negative relationship between the apolipoprotein (ApoE) ε4 allele and brain integrity in HIV-infected (HIV+) individuals, although the presence of this relationship across adulthood remains unclear. The purpose of this study is to clarify the discrepancies using a large, diverse group of HIV+ individuals and multiple imaging modalities sensitive to HIV. The association of ApoE ε4 with structural neuroimaging and magnetic resonance spectroscopy (MRS) was examined in 237 H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Analysis of CHARTER and MACS participants found no association of APOE status with development of cognitive impairment, or with imaging abnormalities in either structural or metabolic brain imaging. [3840] A major reservation about these cohort analyses is the relatively young age, which might limit the power to detect APOE4 effects. In another recent report, while APOE4 was again not associated with HAND, it was associated with abnormal CSF-abeta42 levels, consistent with increased risk of developing AD with further aging.…”
Section: Biomarkers and Handmentioning
confidence: 99%
“…Analysis of CHARTER and MACS participants found no association of APOE status with development of cognitive impairment, or with imaging abnormalities in either structural or metabolic brain imaging. [3840] A major reservation about these cohort analyses is the relatively young age, which might limit the power to detect APOE4 effects. In another recent report, while APOE4 was again not associated with HAND, it was associated with abnormal CSF-abeta42 levels, consistent with increased risk of developing AD with further aging.…”
Section: Biomarkers and Handmentioning
confidence: 99%
“…Our understanding of amyloid metabolism during HIV-1 infection is further clouded by conflicting reports on the association between HAND development and Apolipoprotein E (ApoE) expression, which is a significant risk factor for abnormal amyloid deposition resulting in sporadic AD development (Kim et al, 2009;Morris et al, 2010). While some early reports demonstrate increased frequencies of HAD development in ApoE carriers, more recent studies do not find a correlation between ApoE phenotype and HAND development characterized by either neurocognitive impairments or detrimental neuroimaging outcomes (Burt et al, 2008;Cooley et al, 2016;Corder et al, 1998;Morgan et al, 2013;Valcour et al, 2004b). These differential results could be due to disparities in stages of neurocognitive impairments examined (HAD vs. milder forms of HAND) or in ages of study subjects since ApoE was shown to be an independent risk factor for HAD in HIV-infected patients who are 50 year of age and older, but not in younger subjects (Valcour et al, 2004a).…”
Section: Hiv-1 Infection Affects Cellular Metabolism In Microgliamentioning
confidence: 99%
“…One such report from the CHARTER group (mean age = 40 years, 25% over age 50 years) finds no difference in HAND prevalence between ApoE ε4 carriers and non-carriers nor did they identify neuroimaging differences by carrier status. 19,20 Similarly, investigations from the Multicenter AIDS Cohort Study (MACS, with mean ages at enrollment across groups between 30 to 40 years) do not identify an impact of ApoE ε4 on development of cognitive impairment among participants who tested normal at baseline. 21 One group carefully tested the hypothesis that age may influence the association between ApoE ε4 carrier status and cognitive outcomes using data from the National NeuroAIDS Tissue Consortium (NNTC) noting detrimental effects on HAND diagnosis, executive functioning and information processing in older age (> 50 years) but not in those of younger age.…”
Section: Introductionmentioning
confidence: 99%